Penelitian tentang Dampak Budaya Organisasi, Pengembangan Karir, dan Motivasi Kerja terhadap Kepuasan Kerja Pegawai di Dinas Perumahan Rakyat Kabupaten Sumenep - Rajendra Saputra (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
This research aims to analyze the impact of organizational culture, career development, and work motivation on employee job satisfaction at the Sumenep Regency Public Housing Service. Data was collected through a questionnaire distributed to the Department's employees. Regression analysis is used to evaluate the relationship between the independent variables (organizational culture, career development, and work motivation) and the dependent variable (job satisfaction). The research results show that a positive organizational culture, clear career development opportunities, and high work motivation significantly contribute to the level of employee job satisfaction at the Sumenep Regency Public Housing Service.